Shedding light on the second order nonlinear optical responses of commercially available acidic azo dyes for laser applications. (June 2022) - Asif, Muhammad Fahid; Bano, Rehana; Farooq, Robina; Muhammad, Shabbir; Mahmood, Tariq; Ayub, Khurshid; Tabassum, Sobia; Gilani, Mazhar Amjad
Abstract: Nonlinear optics is a field of immense scientific interest and research owing to its extensive applications in photonics and optoelectronics. NLO materials are crucial components of optical fibers, optical computing, data processing devices, optical sensors, optical modulators, high density optical storage devices, and ultra-fast optical switches. Herein, five commercially available azo dyes, Acid Orange 5, Acid Orange 61, Direct Red 111, Food Yellow 6 and Metanil Yellow are theoretically investigated for their electronic and nonlinear optical properties using density functional theory (DFT) methods. Each azo dye exhibits one alkaline and two acidic forms therefore, all three forms of these azo dyes are considered for calculations. FMO analysis shows reduced HOMO-LUMO energy gaps ( E g ) for acidic forms as compared to alkaline forms. The lowest HOMO-LUMO energy gap of 2.54 eV is observed for AO61 AC I acidic form. Furthermore, the effect of protonation of the dyes on nonlinear optical (NLO) responses are thoroughly investigated. The results at CAM-B3LYP/6-311+G(d) show that the protonation brings significant increase in nonlinear optical response. The highest first hyperpolarizability is observed for DR111 AC II ( β o  = 2.6 × 10 4 au ). The lowest hyperpolarizability calculated for Acid Orange 61 is even greater than that of the prototype, p -nitroaniline (1.2 × 10 3 au ). TD-DFT calculations are also carried out to find first hyperpolarizabilities β o by using two-level-model. The variations in dipole moments and excitation energies are the decisive factors for the increased first hyperpolarizabilities. In order to find the practical applications of the dyes in the field of nonlinear optics, dynamic hyperpolarizabilities for hyper-Rayleigh scattering (HRS), second harmonic generation (SHG) and electro-optical Pockel's effect (EOPE) are computed at a varying range of incident wavelengths. The results are found to be quite supportive for application of the studied azo dyes in second harmonic generation phenomenon. Graphical abstract: Image 1 Highlights: The electronic and nonlinear optical properties of five acidochromic azo dyes are investigated by using DFT simulations. The highest first hyperpolarizability ( β o ) up to 2.6 × 10 4 au is observed for Direct Red Acidic II form. All the selected azo dyes have shown hyperpolarizabilities greater than that of the prototype p -nitroaniline. The highest Hyper-Rayleigh scattering ( β HRS ) value of 2.5 × 10 5 au is obtained for Direct Red Acidic II form at 1600 nm.